2006
DOI: 10.1111/j.1440-1819.2006.01525.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological burdens are associated with young male transsexuals in Korea

Abstract: The purpose of this study was to compare differences of the psychological burdens between young male transsexuals and age-gender matched non-transsexuals with standardized psychiatric rating scales in Korea. A total of 43 biologically unrelated young male transsexuals and 49 age-gender matched non-transsexuals participated in the study. All subjects completed Beck's Depression Inventory (BDI), Social Avoidance and Distress Scale (SADS), Self-Esteem Scale (SES) and Family Adaptability and Cohesion Evaluation Sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 20 publications
2
17
1
Order By: Relevance
“…There were no significant differences for this variable, which is consistent with the findings from other studies which also found no significant differences between MtF and FtM with respect to previous psychiatric treatment (De Cuypere et al, 1995;Dixen et al, 1984;Landen et al, 1998). Violent acts are experienced frequently by transgenders (Kim et al, 2006) and the LGB population (Kosciw et al, 2009;Toomey, Ryan, Diaz, Card, & Russell, 2010), and has been associated with social intolerance (Bergero-Miguel et al, 2008;Grossman & D'Augelli, 2006), even at an early age (Carver, Yunger, & Perry, 2003).…”
Section: Mental Healthsupporting
confidence: 89%
See 1 more Smart Citation
“…There were no significant differences for this variable, which is consistent with the findings from other studies which also found no significant differences between MtF and FtM with respect to previous psychiatric treatment (De Cuypere et al, 1995;Dixen et al, 1984;Landen et al, 1998). Violent acts are experienced frequently by transgenders (Kim et al, 2006) and the LGB population (Kosciw et al, 2009;Toomey, Ryan, Diaz, Card, & Russell, 2010), and has been associated with social intolerance (Bergero-Miguel et al, 2008;Grossman & D'Augelli, 2006), even at an early age (Carver, Yunger, & Perry, 2003).…”
Section: Mental Healthsupporting
confidence: 89%
“…The mean score on the BDI test was higher in the transsexual sample compared with a sample (M = 5.93) of Spanish non-transsexual men and women (Sáenz & Vázquez, 1998). However, in the study by Kim et al (2006), the BDI score (M = 21.4) in transsexuals was considerably higher than in this study. Regarding the predictor variables of depression in transsexuals, the results were in line with studies conducted on non-transsexuals in which depression was related to interpersonal difficulties, unemployment or unpaid work and other mental health comorbidities (Bellón et al, 2011).…”
Section: Mental Healthcontrasting
confidence: 83%
“…I sought to include studies from as many different countries as possible. I identified 22 eligible studies from 16 countries: Belgium (De Cuypere, Jannes, & Rubens, 1995), Brazil (Petry et al 2007), Canada (Blanchard & Sheridan, 1992), Germany (Eicher, Schmitt, & Bergner, 1991;Pfäfflin & Junge, 1990), Ireland (De Gascun, Kelly, Salter, Lucey, & O'Shea, 2006), Japan (Okabe et al, 2008), Korea (Kim et al, 2006), Malaysia (Teh, 2001), the Netherlands (Doorn, Poortinga, & Verschoor, 1994;Smith et al, 2005;Verschoor & Poortinga, 1988), Singapore (Tsoi, 1990), Spain (Gómez-Gil, Trilla, Salamero, Godás, & Valdés, in press), Sweden (Landén, Wålinder, Hambert, & Lundström, 1998), Switzerland (Rauchfleisch, Barth, & Battegay, 1998), Thailand (Winter, 2006), the United Kingdom (Green & Young, 2001;Muirhead-Allwood et al 1999), and the United States (Lawrence, 2005;Rehman, Lazer, Benet, Schaefer, & Melman, 1999;Schroder & Carroll, 1999). Data from these studies are summarized in Table 2.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, in individualistic countries, homosexual men who seek sex reassignment are likely to do so at younger ages than nonhomosexual men (Lawrence, 2005;Smith et al, 2005), usually by their late 20s. In collectivistic countries, homosexual men who undergo sex reassignment or begin living as women often do so in their teens or early 20s (Kim et al, 2006;Tsoi, 1990;Winter, 2006). Homosexual men this young are unlikely to hold positions of responsibility or influence in their societies.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation